Identification of new events in Apollo 16 lunar seismic data by Hidden Markov Model‐based event detection and classification. Issue 10 (5th October 2015) - Knapmeyer‐Endrun, Brigitte; Hammer, Conny
Abstract: Detection and identification of interesting events in single‐station seismic data with little prior knowledge and under tight time constraints is a typical scenario in planetary seismology. The Apollo lunar seismic data, with the only confirmed events recorded on any extraterrestrial body yet, provide a valuable test case. Here we present the application of a stochastic event detector and classifier to the data of station Apollo 16. Based on a single‐waveform example for each event class and some hours of background noise, the system is trained to recognize deep moonquakes, impacts, and shallow moonquakes and performs reliably over 3 years of data. The algorithm's demonstrated ability to detect rare events and flag previously undefined signal classes as new event types is of particular interest in the analysis of the first seismic recordings from a completely new environment. We are able to classify more than 50% of previously unclassified lunar events, and additionally find over 200 new events not listed in the current lunar event catalog. These events include deep moonquakes as well as impacts and could be used to update studies on temporal variations in event rate or deep moonquakes stacks used in phase picking for localization. No unambiguous new shallow moonquake was detected, but application to data of the other Apollo stations has the potential for additional new discoveries 40 years after the data were recorded. Besides, the classification system could be useful for future seismometer missions to other planets, e.g., the InSight mission to Mars. Key Points: Successful application of HMM‐based event detection and classification to Apollo lunar seismic data Detection of over 200 new events (deep moonquakes, impacts) in 3 years of Apollo 16 data Demonstrate way to flag previously undefined signal class (e.g., shallow moonquake) as new event type